Beginning Android web apps development develop for Android using HTML5, CSS3, and JavaScript - Westfall, Jon; Allen, Grant; Augusto, Rocco ([Berkeley, CA] Apress New York Distributed to the book trade worldwide by Springer Science+Busines Media, 2012)
With Beginning Android Web Apps Development, you'll learn how to apply HTML5, CSS3, JavaScript, Ajax and other Web standards for use on the Android mobile platform, by building a variety of fun and visually stimulating games and other web applications! If you've done some basic web development, and you want to build your skills to create exceptional web apps, you'll find everything you seek in the discussions and examples in this book--
Harnessing the power of the mobile web -- Twitter applications : who's that tweet? -- Twitter applications : I love ham -- Basic planning and structuring of your application -- Handling multiple screen resolutions with CSS3 -- Handling different browser platforms -- Building an impressive user experience with jQuery Mobile -- Building visually rich internet applications -- HTML5 location-based applications -- Using cloud services : a transport application -- Pushing the limits with audio and video -- Supercharging the user experience with AJAX -- Packaging your applications
Includes index
1
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing